2011
DOI: 10.5402/2011/709653
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ADHD Symptoms amonge Male Preschoolers Based on Different Informants in Ahvas City of Iran

Abstract: Background. This cross-sectional study evaluated rate of reported ADHD symptoms among male preschoolers in Ahvaz by different informants and rate of their agreement. Method. One hundred ninety-two 5-6-year old boys from nine kindergartens in Ahvaz were selected. Teacher and parents' Conners ADHD rating scales were used. Findings. For 133 children, questionnaires were returned. Prevalence of children with positive questionnaire was 24.06%, with only parent questionnaire was 4.51%, with only teacher questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…5,6 Primarily, parents and then teachers are the most important individuals who establish the strongest relationship with these children; therefore, parents and kindergarten instructors and teachers of preschool centres are considered as the most important sources for the ADHD assessment at this age group specially for gathering information for better psychological and psychiatric evaluations; 7 however, there is little agreement between the assessment of parents and the teachers concerning the diagnosis of ADHD symptoms. 7,8 Therefore, simultaneous review of parents' and teacher's reports seems to be one of the ways to reduce the ADHD screening error, as they provide valuable information, which can be helpful for authentic diagnosis. A review study which was carried out on the previous studies, estimated ADHD prevalence in pre-school boys in Ahvaz-Iran using the Conners scale and the results showed that the prevalence rate was 24.06 per cent, 4.51 per cent, 17.29 per cent and 2.25 per cent based on the positive rating scale, parent form, only teacher questionnaire and both parent and teacher questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Primarily, parents and then teachers are the most important individuals who establish the strongest relationship with these children; therefore, parents and kindergarten instructors and teachers of preschool centres are considered as the most important sources for the ADHD assessment at this age group specially for gathering information for better psychological and psychiatric evaluations; 7 however, there is little agreement between the assessment of parents and the teachers concerning the diagnosis of ADHD symptoms. 7,8 Therefore, simultaneous review of parents' and teacher's reports seems to be one of the ways to reduce the ADHD screening error, as they provide valuable information, which can be helpful for authentic diagnosis. A review study which was carried out on the previous studies, estimated ADHD prevalence in pre-school boys in Ahvaz-Iran using the Conners scale and the results showed that the prevalence rate was 24.06 per cent, 4.51 per cent, 17.29 per cent and 2.25 per cent based on the positive rating scale, parent form, only teacher questionnaire and both parent and teacher questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that 63% of elderlies with ADHD also suffered from psychiatric disorders, came from lower educational backgrounds, had poor job performance, and were socially more isolated. Older ones had more problems in productivity and their outlook in life [ 6 ]. However, little is known about ADHD among the elderly, and because ADHD in elderlies is a relatively new mental health disorder, a valid screening tool is required [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit hyperactivity disorder (ADHD) is a common psychiatric disease with a worldwide pooled prevalence of 5.29% ( 1 ). Two population-based epidemiological studies in Iran found that 15% of preschoolers had ADHD symptoms ( 2 , 3 ). According to the research conducted by the American Academy of Child and Adolescents, ADHD in preschool children is a relatively stable diagnosis; thus, it needs long-term or repeated episodes of behavioral and pharmacological therapies ( 4 ).…”
Section: Introductionmentioning
confidence: 99%